Mycorrhizal types influence island biogeography of plants - Delavaux, Camille S; Weigelt, Patrick; Dawson, Wayne; Essl, Franz; van Kleunen, Mark; König, Christian; Pergl, Jan; Pyšek, Petr; Stein, Anke; Winter, Marten; Taylor, Amanda; Schultz, Peggy A; et al. (Communications biology, 2021)
Plant colonization of islands may be limited by the availability of symbionts, particularly arbuscular mycorrhizal (AM) fungi, which have limited dispersal ability compared to ectomycorrhizal and ericoid (EEM) as well as orchid mycorrhizal (ORC) fungi. We tested for such differential island colonization within contemporary angiosperm floras worldwide. We found evidence that AM plants experience a stronger mycorrhizal filter than other mycorrhizal or non-mycorrhizal (NM) plant species, with decreased proportions of native AM plant species on islands relative to mainlands. This effect intensified with island isolation, particularly for non-endemic plant species. The proportion of endemic AM plant species increased with island isolation, consistent with diversification filling niches left open by the mycorrhizal filter. We further found evidence of humans overcoming the initial mycorrhizal filter. Naturalized floras showed higher proportions of AM plant species than native floras, a pattern that increased with increasing isolation and land-use intensity. This work provides evidence that mycorrhizal fungal symbionts shape plant colonization of islands and subsequent diversification.
Keywords: rostliny; mykorhiza; Plants; Plant Dispersal; Mycorrhizae; biodiverzita; symbióza; distribuce rostlin; Symbiosis; Plant Physiological Phenomena; fyziologie rostlin; Biodiversity